A Review of the Status of Spatial Data Infrastructure Implementation in Africa - Makanga, Prestige; Smit, Julian (Computer Society of South Africa, 2022)
Spatial data is a key resource for the development of a nation. There is a lot of economic potential that is locked away in spatial data collections and this potential is realised by making the data widely available. Spatial Data Infrastructures (SDI) provide a platform for spatial data users, producers and those that manage it, to distribute the data more efficiently. Governments all over the world are realising the value of National Spatial Data Infrastructures (NSDI), and therefore making major investments to establish them. However, in Africa, implementation of formal NSDI is being done at a seemingly slow pace. This paper presents an assessment of the status of NSDI activity in Africa. 29 countries were used in the survey and an assessment was made per region (South, West, East, North and Central Africa). The results show that generally, formal NSDI activity in most African countries is still in its infancy. The paper also gives recommendations of possible measures that can be taken to foster SDI implementation on the continent. In addition, it highlights potential areas for further SDI research.